THE DEVELOPMENT OF AN OPERATIONS MANUAL INFORMATION SYSTEM FOR STUDENT AFFAIRS ADMINISTRATIVE ENCOURAGEMENT IN KOHSAMUI SCHOOL UNDER THE SECONDARY EDUCATIONAL SERVICE AREA OFFICE SURATTHANI CHUMPHON - Nuprain, Patcharin; Yotharak , Maliwan; Samakkhi, Pricha (Journal of Educational Review Faculty of Education in MCU, 2025)
This research aims to 1) study the student affairs administration of Koh Samui School, 2) develop a manual for information system operations to promote student affairs administration of Koh Samui School, and 3) present the use of the manual for information system operations to promote student affairs administration of Koh Samui School, Surat Thani-Chumphon Secondary Education Area Office. This research was conducted using qualitative methods by conducting in-depth interviews with 15 relevant persons, in-depth interviews with 5 experts to draft guidelines, and focus groups with 7 experts to assess feasibility, appropriateness, and usefulness. The qualitative data were analyzed using content analysis. The research results found that: 1) The student affairs administration of Koh Samui School is located in a special area, resulting in continuous personnel transfers and the need to allocate new personnel to fill vacant positions, especially in the student affairs administration department, which is responsible for taking care of, monitoring, and assisting students in terms of guidance, activities, administration, and welfare. When personnel are changed frequently, operations are inconsistent and delayed, affecting the efficiency of student affairs administration. Which has not been implemented fully and efficiently as it should be. 2) Information system operation manual for promoting student administration of Koh Samui School, consisting of (1) guidance work (2) student activities work (3) administration work (4) student welfare work, all 4 areas have organized information systems for student administration in a systematic manner, namely, data collection, data verification, data processing, information storage, information presentation, and information application. And 3) Presentation of the use of the information system operation manual for promoting student administration of Koh Samui School, Surat Thani-Chumphon Secondary Educational Service Area Office, found that it is possible, appropriate, and useful in promoting student administration of Koh Samui School.